Bilirubin as a predictor of diseases of civilization. Is it time to establish decision limits for serum bilirubin concentrations? - Vítek, Libor (Archives of biochemistry and biophysics, 2019)
Bilirubin is among the most potent of the endogenous antioxidants. Data developed over the last three decades have convincingly demonstrated the protective effects of mildly elevated serum bilirubin concentrations; whereas lower levels of it have been associated with an increased risk of various diseases of civilization, commonly accompanied with increased oxidative stress. Even tiny, micromolar changes of serum bilirubin concentrations have been associated with substantial modulation for the risk of these diseases. However, clinical data published in the current literature are influenced by many confounding factors that have not been properly controlled for. These include the use of improper reference intervals, which are mostly used as common intervals without any partitioning for gender, ethnicity, age, or other important factors (such as smoking). The clinical chemistry methods used for bilirubin determination have not been standardized; in fact, these methods are known to be among the least reliable of any used in clinical chemistry labs. As a result, the data from epidemiological studies are not always comparable. Therefore, it is highly recommended to conduct properly-designed large epidemiological studies. Based on this data, the establishment of decision limits is highly warranted, especially for the lower concentration values of serum bilirubin.
Keywords: Reference interval; Physiological concentrations; senioři; bilirubin; Aged; Male; lidé; Risk factor; Humans; Diagnosis; Predictor; referenční hodnoty; Decision limits; Reference Values; Young Adult; Biomarkers; senioři nad 80 let; Clinical Decision Rules; Aged, 80 and over; mužské pohlaví; mladý dospělý; diagnóza; biologické markery; pravidla klinického rozhodování; ženské pohlaví; Bilirubin; Female; Diseases of civilization